2022
DOI: 10.1101/2022.06.06.494964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpretable XGBoost-SHAP model predicts the nanoparticles delivery and reveals its interaction with tumor genomic profiles

Abstract: Understanding the complex interaction between nanoparticles (NPs) and tumors in vivo and how it dominates the delivery efficacy of NPs is critical for the translation of nanomedicine. Herein, we proposed an interpretable XGBoost-SHAP model by integrating the information of NPs physicochemical properties and tumor genomic profile to predict the delivery efficacy. The correlation coefficients were > 0.99 for all training sets, and 0.830, 0.839, and 0.741 for the prediction of maximum delivery efficacy (DEmax)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…448 The most common posthoc analysis methods used in nanotoxicology applications are permuted feature importance 134,145,368,420,443,449 and SHAP. 92,410,450,451 The permuted feature importance is a model-agnostic global explanation method that provides insights into ML model behavior. It estimates and ranks feature importance by evaluating how the prediction error increases when a feature is unavailable.…”
Section: Applications Of ML To Mechanism Analysis Inmentioning
confidence: 99%
See 2 more Smart Citations
“…448 The most common posthoc analysis methods used in nanotoxicology applications are permuted feature importance 134,145,368,420,443,449 and SHAP. 92,410,450,451 The permuted feature importance is a model-agnostic global explanation method that provides insights into ML model behavior. It estimates and ranks feature importance by evaluating how the prediction error increases when a feature is unavailable.…”
Section: Applications Of ML To Mechanism Analysis Inmentioning
confidence: 99%
“…Various ML models have been developed for the in vivo behavior of NMs in mice or rats. These include modeling of reproductive and pulmonary toxicity, ,, genotoxicity, tissue-specific oxidative stress, metabolic pathways, delivery efficiency, and in vivo fate. ,,, For example, an RF model was developed to identify the most important factors determining reproductive toxicity of NPs, determined by the sperm count, percentage of motile sperm, and sperm abnormalities in rats . Feature importance analysis revealed that the reproductive toxicity was strongly related to the NP type and toxicity end points used.…”
Section: Unraveling Quantitative Nanostructure–toxicity Relationships...mentioning
confidence: 99%
See 1 more Smart Citation